Effect of trust in leadership on team effectiveness and performance in Iranian Futsal Super League players - Najafzadeh, Y.; Zarei, A.; Azadfada, S.; Doroudian, AA. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The purpose of the study was to examine the effect of trust in leadership on team effectiveness and performance in Iranian Futsal Super League players. The sample consisted of all the male players of the Iranian Futsal Super League in 2017-2018 (n=163). The participants completed the following questionnaires: 1) Leadership Confidence Questionnaire. 2) Team Effectiveness Questionnaire. 3) Subjective performance evaluation. Descriptive and inferential statistics were used to analyze the data. The results indicated that trust in the coach had a significant positive effect for the players on team effectiveness (sig = 0.001, t = 5.869) and on team performance (sig = 0.001, t = 7.194). In conclusion, in order to gain the trust of the team, the coaches should be able to make the right decisions in different situations and have the necessary skills and qualities (justice, benevolence, honesty, and ability), which in turn results in higher team effectiveness and team performance.